The Influence of Principal Leadership and Teacher Self-Development on the Professional Competence of Public High School Teachers - Martono, Rudy; Soedjono, Soedjono; Prayito, Muhammad (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study investigates the influence of principal leadership and teacher self-development on the professional competence of public senior high school teachers in Rembang Regency. Employing a quantitative research approach with a correlational ex post facto design and a survey method, data were collected through validated Likert-scale questionnaires from a sample of 214 teachers, selected using purposive and proportionate stratified random sampling from a total population of 460 teachers. The data were analyzed using SPSS through simple and multiple linear regression, correlation, and coefficient of determination analysis. The findings indicate that both principal leadership and teacher self-development have significant and positive effects on teacher professional competence, both individually and simultaneously. Principal leadership contributes 49.5% to competence (r = 0.704), with participative leadership as the strongest dimension and collaboration-building as the weakest. Teacher self-development contributes 48.8% (r = 0.698), with knowledge improvement as the most influential factor and teacher reaction as the least. Jointly, both variables explain 54.7% of the variance in professional competence (R = 0.740). Among the competence dimensions, monitoring student learning outcomes had the strongest influence, while commitment to students and the learning process was the weakest. These findings emphasize the importance of fostering participative leadership and promoting continuous self-development to enhance teacher performance and educational quality.